Original paperHeart rate variability in adult patients with congenital heart disease - Trojnarska, Olga; Bręborowicz, Piotr; Łanocha, Magdalena; Lesiak, Maciej; Bryl, Wiesław; Cieśliński, Andrzej (Archives of Medical Science, 2005)
Introduction: Heart rate variability (HRV) illustrates an autonomic nervous system influence on the sinus node. It is known that low HRV parameters indicate poor prognosis in patients with myocardial infarction, predict sudden cardiac death and death due to heart failure. Adult population with congenital heart disease (CongHD) is particularly exposed to these complications. The aim of this study was to evaluate HRV parameters in adult patients with CongHD and to analyse the impact of the specific type of CongHD and past cardiac surgery on HRV. Materials and methods: Data of 345 adult patients aged 18-67 with CongHD were analysed. From the 24-hour ECG monitoring time domain indexes of HRV were calculated: SDNN, SDANN-i, SDNN-I, r-MSSD, pNN50. Results: All analysed HRV parameters were not different in CongHD patients comparing to the control group, and gradual, physiologic decrease due to aging was also present. Age at operation had no effect on HRV values, except in patients after correction of coarctation of the aorta (SDNNi r=-0.312; p=0.005; rMSSD r=-0.354; p=0.001; pNN50 r=-0.41; p=0.0001) and ventricular septal defect (rMSSD r=-0.310; p=0.02; pNN50 r=-0.336; p=0.01), where a negative correlation was found. Conclusions: 1. Despite slight differences between subgroups of CongHD patients, HRV values in adult patients with CongHD are similar to those in the healthy population, and gradual, physiologic decrease due to aging is also present. 2. Age at operation does not influence the HRV profile in the general population of patients with CongHD. Age at operation influences HRV in patients with left ventricle overload. Similar relations are not observed in the group with impaired right ventricle hemodynamics.